Strata ownership resorts and the investment decision as a question of capital budgeting : a proposed method's application in Phuket Luxury tourism accommodation - Amos Mabey, James (Prince of Songkla University, 2021)
Thesis (M.B.A., Hospitality and Tourism Management)--Prince of Songkla University, 2010